Historicizing Political Dichotomy Among the Double Unilineal but Prevalently Matrilineal Cross River Igbo (British Journal of Multidisciplinary and Advanced Studies, 2023)
The patrilineally-biased socio-political system was prevalent among the Igbo; and was the preserve of adult males above the ages of eighteen. It legislated on the decisions of the paramount Eze and the Council of Elders. The womenfolk were hardly politically visible enough in decision-making as it affected them. Yet, among the double unilineal Cross River Igbo, such as the Abam, Abiriba, Amaseri, Ihechiowa, Ohafia and Ututu, the womenfolk were politically as active as the men. Their decisions which were usually backed by women-specific deities, such as Odamini Ufuforo, Imohuma, Ohuhu and Ibara; and institutionalized social control mechanisms, such as Abiamkpu, Ibuo Okpu and Use, were often incontrovertible. A gendered political dichotomy entailed specific domains of contestations, well-defined political functions for the men and womenfolk; and cultural exhibits that portrayed the audacity of firmness, authority and visibility. Except in the choice of the paramount chief from among the apical patrilineages, the socio-economic and political systems of the Cross River Igbo were suffused by matriliny through which descent and inheritance were acquired and traced. Authority laid more on those who owned more lands and were more numerous. The matrilateral (horizontal) distributive justice system and the ability principles were preferred over the patrilateral (vertical) distributive justice system. Moreover, members of the patrilineages equally belonged to their mothers’ matrilineages where they stood to access more lands, acceptability and relevance in a double unilateral distributive justice system. The paper concluded that it was impossible for the females under the aegis of the matrilineages to be politically invisible since they had certain socio-economic advantages, therefore, political. Oral interviews predominated in the research while written sources served complementary and subsidiary purposes.